Analisis Hukum Pencabutan Izin Usaha Leasing Oleh Otoritas Jasa Keuangan: Studi Kasus: PT SME Finance Indonesia - Nanur Faridatul Ummah; Nindya Wahyu Wanodya; Regio Bhisma Abiyosa; Emma Yunika Puspasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The operational license of PT Sarana Majukan Ekonomi Finance Indonesia (PT SMEFI) has been revoked through a Decree from the OJK Board of Commissioners with the number KEP-2/D.06/2024, which was issued on January 15, 2024. This decision was taken because PT SMEFI was declared a company whose condition could not be improved. Prior to the revocation of the business license and the decision was made, the OJK had classified PT SMEFI as a company under intensive supervision as a result of an overall evaluation of the company's health which was considered unfavorable. PT SMEFI has also received administrative sanctions in the form of a Third Warning due to violations of the provisions of the applicable provisions, namely regarding the Financing to Asset Ratio (FAR). Every action carries legal consequences that must be accounted for. Leasing, as a form of financing in the financial sector, is required to comply with existing regulations, including operational permits issued by the Financial Services Authority (OJK). Regarding permits, it is the legal basis for leasing companies to carry out their operations.